Designing A Proposed Organizational Climate Model : The Case of the Workplaces of Civil Servants, Kingdom of Cambodia : - Ol, Ro; Phothikitti, Kitti; Fernando, Maria Socorro C (ABAC ODI JOURNAL Vision. Action. Outcome, 2023)
The study has three objectives: (1) to determine the influence of structure, warmth, support, identity and reward on the perceived workplace organizational climate (PWOC); (2) to explore influence of PWOC on job performance; and (3) to design a proposed model for organizational climate (OC) for Cambodian Civil service workplaces based on the findings. A cross-sectional design approach and a quantitative approach were applied in the research study. Structural Equation Model were utilized to conduct statistical analysis and to analyze the relationships between the measured variables, and latent constructs as well as to construct the model. The results indicate that there were four OC factors, such as structure, warmth, support and identity, that provide significant influence on the PWOC at the level of .05. Also, it is found that these four factors show significant and positive impact on job performance as mediated by the PWOC. Then, a proposed OC Model for workplaces of Cambodian civil servants was drawn from the findings of the study. The study recommends further research, taking into account different kinds of organizations including government or non- governmental organizations or private sector institutions, and by applying a mixed-method approach.